Pendampingan Pengembangan UMKM melalui Implementasi Financial Technology Era Society 5.0 - Hamzah, A. Hadian Pratama; Kaligis, Jenny Nancy; Yahya, Sitti Rachmawati; Waoma, Samalua; Samosir, Hendrik ES; Alfiana, Alfiana; Nurhasanah, Nurhasanah (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
UMKM plays an important role in the economy of a region or country. Financial technology is one of the important roles to change behavior and expectations and can increase the quality and number of UMKM actors. This dedication aims to provide understanding, improvement, and quality improvement for UMKM actors through improvements in terms of standard and good financial management. The method used in this community service is Community Based Research (CBR) using the Forum Group Discussion (FGD) approach. The results of the activity show that some UMKM actors still do not understand the importance of Financial Technology (FinTech) in the business world, especially in terms of financial management.